Mathematical principles of the internet - Bhatnagar, Nirdosh (Boca Raton, FL : CRC Press, 2019)
The purpose of these books is to provide mathematical principles of Internet engineering. They do not aim to provide all of the mathematical foundations upon which the Internet is based. Rather, they cover a partial panorama and key principles. The book is divided into two parts. Volume 1 explores Internet engineering. The supporting mathematics is covered in Volume 2. The chapters on mathematics complement those on the engineering episodes. An effort has been made to provide justification and informal proofs as much as possible. Each chapter also begins with a portrait and a brief account of the work of a prominent mathematician/scientist/engineer--
V. 1. Engineering fundamentals. -- v. 2. Mathematical concepts.
OCLC-licensed vendor bibliographic record.
Keywords: Internetworking (Telecommunication) -- Mathematics; Computer science -- Mathematics; Internet -- Mathematical models